Plasminogen Activator Inhibitor-1 (PAI-1) Promoter 4G/5G Genotype and Increased PAI-1 Circulating Levels in Postmenopausal Women with Coronary Artery Disease - Grancha, S.; Estellés, A.; Tormo, G.; Falco, C.; Gilabert, J.; España, F.; Cano, A.; Segui, R.; Aznar, J. (Thrombosis and Haemostasis, 1999)
Increased circulating levels of type 1 plasminogen activator inhibitor (PAI-1) have been associated with coronary artery disease (CAD). However, genetic and environmental determinants of PAI-1 expression are only partially understood. The levels of PAI-1 have been found to relate to 4/5 guanosine (4G/5G) polymorphism in the promoter region of the PAI-1 gene. The 4G allele in this polymorphism has been associated with higher levels of plasma PAI-1 activity, but despite the strong correlation between PAI-1 activity and antigen, no association has been found between PAI-1 antigen levels and the PAI-1 promoter 4G/5G genotype. The aim of the present study was to analyze the influence of the PAI-1 promoter 4G/5G genotype on PAI-1 levels in post-menopause women with coronary disease in comparison with healthy women in pre and postmenopausal status, and the influence of this genotype on variations in PAI-1 levels after hormone replacement therapy (HRT). No differences between 4G/5G allele distribution in the groups studied were observed. The group of postmenopausal women with CAD showed significantly increased PAI-1 antigen and activity levels in comparison with the control groups, and the levels of PAI-1 correlated with the 4G/5G genotype. A multivariate analysis revealed that in the CAD group there was a high correlation between 4G allele dosage and PAI-1 antigen levels, which were also influenced by the triglyceride levels but not by estrogen or glucose levels. After hormone replacement therapy the decrease in PAI-1 levels was correlated with the 4G allele dosage. We conclude that in the group of postmenopausal women with CAD the influence of the PAI-1 promoter 4G/5G genotype on PAI-1 levels is more evident than in the control groups, and that the decrease in PAI-1 levels after HRT in CAD women correlates with the 4G allele dosage.